A fuzzy AHP based decision support system for disaster center location selection and a case study for Istanbul - (:unkn) unknown (My University, 2011)
Purpose: The purpose of this paper is to propose a disaster logistics center location selection decision support system, based on analytic hierarchy/fuzzy analytic hierarchy process methods, which will serve to fulfill the needs of disaster victims and rescue teams after a possible earthquake, and to implement the proposed systems for Istanbul. Design/methodology/approach: Determining the appropriate location from among the possibilities by taking many sophisticated and inter-related processes and parameters into consideration under stringent constraints is one of the keystones of logistics. Disaster logistics center location selections are extremely complex and vital. In this paper, analytic hierarchy/fuzzy analytic hierarchy process methods are used to compose a decision support system for determining the location of disaster logistics centers. The criteria and the weighting for the criteria that are used are determined via a questionnaire technique applied to specialists working in the Istanbul Center of Disaster Coordination. Findings: Results gathered from the implementation of the proposed models to the chosen case illustrate that systems successfully determine the location, and both models point out the same result with different weights. Originality/value: The paper introduces two disaster logistics center location selection decision support systems (fuzzy and crisp) and presents an empirical case study of the proposed models for Istanbul. The proposed model and outcomes from the application may shed light on future work, especially in the field of disaster logistics management. © Emerald Group Publishing Limited.
Keywords: Analytical hierarchy process; Decision support systems; Disasters; Emergency logistics; Emergency response; Fuzzy AHP; Location selection